Factors that contribute to physician burnout, interventions to prevent and mitigate burnout and knowledge gaps—a Delphi study - Simões, Catarina; Fronteira, Inês; Pedro, Ana Rita (Frontiers in Public Health, 2025)
IntroductionBurnout among physicians is a worldwide concern issue, impacting individual well-being and healthcare efficiency and jeopardizing the achievement of Universal Health Coverage. Using the Portuguese National Health Service scenario, we aimed at identifying the factors that contribute to burnout of physicians and interventions that can be helpful in its prevention.MethodsWe used a Delphi panel technique with three rounds of participation with 16 specialists, including physicians, psychologists, academics and hospital administrators.ResultsOrganizational variables such system strain, staff overload, and unfavourable working circumstances were pointed as the main contributing factors of burnout. Consensus was reached that courses of action, such as resource allocation, legislative changes, and promotion of a healthier workplace environment can help prevent physician burnout. Non-organizational tactics such as workplace amenities and health literacy initiatives were also considered relevant. Identified knowledge gaps comprised long-term effects of burnout, leadership influence, and environmental repercussions.DiscussionThe study concludes that addressing organizational factors and implementing targeted interventions are crucial for improving physician well-being and aiding healthcare efficiency in Portugal but also in similar contexts.